1995
DOI: 10.1016/0092-8674(95)90235-x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic knockouts reveal a critical requirement for pancreatic β cell glucokinase in maintaining glucose homeostasis

Abstract: The secretion of insulin is controlled by the rate of glucose metabolism in the pancreatic beta cells. As phosphorylation by glucokinase (GLK) appears to be the rate-limiting step for glucose catabolism in beta cells, this enzyme may be the glucose sensor. To test this possibility and to resolve the relative roles of liver and beta cell GLK in maintaining glucose levels, we have generated mice completely deficient in GLK and transgenic mice in which GLK is expressed only in beta cells. In mice with only one GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
175
2
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(187 citation statements)
references
References 39 publications
9
175
2
1
Order By: Relevance
“…However, glucokinase could be replaced by other insulin-independent hexokinases, in vivo and ex vivo. In vivo, knocked out mice specifically deficient in glucokinase in liver have an almost normal glucose regulation (32), whereas deficiency in pancreas glucokinase leads to neonatal death from severe insulin-dependent diabetes mellitus (33). Ex vivo, we have shown that hepatoma cells with hexokinase 1 (2, and this paper) respond to glucose in modulating transcription of glucose-responsive genes, e.g.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, glucokinase could be replaced by other insulin-independent hexokinases, in vivo and ex vivo. In vivo, knocked out mice specifically deficient in glucokinase in liver have an almost normal glucose regulation (32), whereas deficiency in pancreas glucokinase leads to neonatal death from severe insulin-dependent diabetes mellitus (33). Ex vivo, we have shown that hepatoma cells with hexokinase 1 (2, and this paper) respond to glucose in modulating transcription of glucose-responsive genes, e.g.…”
Section: Discussionmentioning
confidence: 93%
“…In endocrine pancreas ␤ cells, the predominant glucose-sensor has been definitively identified as glucokinase by knock out of the gene in mice (32,33), and the significance of the specific GLUT 2 expression in rodent ␤ cells is still disputed, especially as the amount of the GLUT 2 isoform seems to be very low in human ␤ cells (34,35). German (36) has shown that ␤ cells overexpressing GLUT 1 do not lose their ability to sense changes in glucose concentration within the physiological range and to respond by an appropriate stimulation of the insulin gene promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodents also support a critical role for GK in glucose homeostasis. Mice that are homozygous for disruption of the GK gene die from diabetes within days of birth, whereas the heterozygotes are hyperglycemic (10,11). Liver-specific GK overexpression in nondiabetic mice improved glucose tolerance (12,13), and in high-fat dietinduced diabetic mice, adenoviral overexpression of GK improved glucose tolerance and decreased fasting blood glucose with concomitant decreased insulin secretion (14).…”
mentioning
confidence: 99%
“…The pancreatic GK isoform is an absolute requirement for survival, as gk del/del (either global or b-cell specific) is lethal, whereas global or b-cell-specific heterozygous (gk del/wt ) deletion causes only modest hyperglycaemia (Bali et al 1995, Grupe et al 1995, Terauchi et al 1995. Deletion of liver GK leads to mild hyperglycaemia but decreases glucose utilisation and glycogen synthesis (Postic et al 1999).…”
Section: Introductionmentioning
confidence: 99%